Transatlantic Cinephilia: Film Culture between Latin America and France, 1945–1965, de Rielle Navitski - Amieva, Mariana (Imagofagia, 2024)
Sobre Navitski, Rielle. Transatlantic Cinephilia: Film Culture between Latin America and France, 1945–1965. California: University of California Press, 2023, 336 pp., ISNB: 9780520391437.